A method to calculate the accumulated volume of transponed masses. - Pool, M. (Cuadernos de Geología Ibérica, 1991)
Investigation of tIte depositional environment of fan-deltas might involve sorne quantative measurements. This program written in Fortran-77 may provide an initial step. TItis particular volume calculation metItod is based on cone shaped bodies or derivative sItapes. Fasis Itave (in tIteir underwater formation) in plan similar sItapes: altItougIt in section tItey are more «fiat cone» sItaped. TItis fact however Itas only a minor influence on the total result.